2021
DOI: 10.3389/fnut.2021.691695
|View full text |Cite
|
Sign up to set email alerts
|

Menthol Mouth Rinsing Is More Than Just a Mouth Wash—Swilling of Menthol to Improve Physiological Performance

Abstract: Interventions that solely act on the central nervous system (CNS) are gaining considerable interest, particularly products consumed through the oral cavity. The oropharyngeal cavity contains a wide array of receptors that respond to sweet, bitter, and cold tastants, all of which have been shown to improve physiological performance. Of late, the ergogenic benefits of carbohydrate (CHO) and caffeine (CAF) mouth rinsings (MRs) have been widely studied; however, less is known about menthol (MEN). That the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 78 publications
0
18
1
Order By: Relevance
“…Such effects have previously been observed following carbohydrate rinsing [ 60 ] and supplementation [ 61 ] prior to exercise. Like carbohydrate rinsing, it has been suggested that menthol may elicit an increase in central drive and an increased sensation of pleasure albeit for a short period of time, potentially aiding performance [ 16 , 62 ]. Menthol is known to influence the drive to breathe and arousal through stimulation of the trigeminal nerves; when this occurs in hot environments this sensation is perceived as pleasant, which in turn may increases central drive and improves work capacity [ 16 , 23 , 24 , 25 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such effects have previously been observed following carbohydrate rinsing [ 60 ] and supplementation [ 61 ] prior to exercise. Like carbohydrate rinsing, it has been suggested that menthol may elicit an increase in central drive and an increased sensation of pleasure albeit for a short period of time, potentially aiding performance [ 16 , 62 ]. Menthol is known to influence the drive to breathe and arousal through stimulation of the trigeminal nerves; when this occurs in hot environments this sensation is perceived as pleasant, which in turn may increases central drive and improves work capacity [ 16 , 23 , 24 , 25 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like carbohydrate rinsing, it has been suggested that menthol may elicit an increase in central drive and an increased sensation of pleasure albeit for a short period of time, potentially aiding performance [ 16 , 62 ]. Menthol is known to influence the drive to breathe and arousal through stimulation of the trigeminal nerves; when this occurs in hot environments this sensation is perceived as pleasant, which in turn may increases central drive and improves work capacity [ 16 , 23 , 24 , 25 , 62 ]. The absence of alterations in VO 2 or VE between solutions is likely due to the maximal nature of the exercise task, eliciting relatively homogenous respiratory outcomes, independent of the solution administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the effect of swilling carbohydrate (CHO) and menthol (MEN) solutions prior to and during exercise is now established. Both tastants have been shown to have an ergogenic effect without requiring ingestion [9][10][11][12]. The level of performance enhancement may vary depending on type and duration of exercise [11], timing, concentration and length of the swill [13].…”
Section: Introductionmentioning
confidence: 99%
“…A review by Gavel et al [10] found 8 of 10 studies utilising a MEN mouth swill improved performance across a variety of protocols (concentrations, durations, environmental conditions, swill frequency, sex). Specifically in cycling time trials, menthol mouth swill significantly improved mean power output (p = 0.034) and 30 km TT performance (2.3%) [22].…”
Section: Introductionmentioning
confidence: 99%